Characterization of p53 From the Marine Crab Portunus trituberculatus and Its Functions Under Low Salinity Conditions - Ren, Xianyun; Wang, Lei; Xu, Yao; Wang, Qiong; Lv, Jianjian; Liu, Ping; Li, Jian (Frontiers in Physiology, 2021)
Portunus trituberculatus, or the swimming crab, is tolerant of reduced salinity; however, the molecular mechanism of this tolerance is not clear. Cells can be damaged by hyperosmotic salinity. The protein p53, sometimes referred to as “the guardian of the genome”, displays versatile and important functions under changing environmental conditions. Herein, the P. trituberculatus p53 gene (designated as Ptp53) was cloned and studied. The full-length Ptp53 cDNA comprised 1544 bp, with a 1314 bp open reading frame, which encodes a putative polypeptide of 437 amino acids. Quantitative real-time reverse transcription PCR assays revealed ubiquitous expression of Ptp53 in all tissues examined, with the gills showing the highest expression. Extensive apoptosis was detected under low salinity conditions using terminal deoxynulceotidyl transferase nick-end-labeling (TUNEL) staining. Oxidative stress was induced under low salinity conditions, consequently leading to apoptosis. Low salinity stress caused significant upregulation of Ptp53 mRNA and protein levels in the gills. Moreover, compared with that in the control group, the mortality of Ptp53-silenced crabs under low salinity stress was enhanced significantly. Taken together, our findings suggest that Ptp53, via regulation of apoptosis and antioxidant defense, has important functions in the low salinity stress response of the swimming crab.